REDISTRIBUSI TANAH YANG BERASAL DARI PELEPASAN KAWASAN HUTAN UNTUK KEPERLUAN KANTOR KEPOLISIAN NEGARA REPUBLIK INDONESIA DI KABUPATEN TANAH DATAR - Dwi Utari, Shindi; Nurdin, Zefrizal; Andora, Hengki (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Land redistribution is a series of activities carried out by the government to distribute and/or grant land rights originating from TORA (Land Objects of Agrarian Reform) to subjects of agrarian reform, accompanied by the granting of land rights certificates. One of the objects of land redistribution is land originating from the release of state forest areas and/or changes in forest area boundaries. The head of the Tanah Datar district land office provides certificates of land use rights resulting from land redistribution activities from the release of forest areas, and the granting of land rights to government agencies, although the objective of agrarian reform should be aimed at the welfare of the people, especially the landless poor. This is the basis for the author to conduct this research. The research questions are: 1) How is the implementation of land redistribution from the release of forest areas for the Indonesian National Police Office in Tanah Datar Regency? 2) What is the basis for granting land rights to the Indonesian National Police Office through land redistribution from the release of forest areas? 3) How is the registration of land rights for the Indonesian National Police Office obtained through land redistribution from the release of forest areas in Tanah Datar Regency? This research uses an Empirical Jurisprudence method with primary data from interviews and field observations, and secondary data from document studies. The research findings show that the implementation of land redistribution in Tanah Datar Regency is based on the technical instructions for land redistribution in 2024 and Presidential Regulation No. 62 of 2023, and provides justice and benefits to the recipients. The granting of land rights to the police agency is based on Decree No. 2/HP/BPN-03.10/2024, with considerations that the land has been controlled by the state and meets the requirements. The land registration process follows the stages of the redistribution process, starting from the submission of files to the issuance of land use rights certificates for public facilities.